GE_GERICHTE P/17633/2014 vom 2. Februar 2016 - GE Cour de justice (2016)
IN DUBIO PRO REO; VOL(DROIT PÉNAL); TENTATIVE(DROIT PÉNAL); COMPLICITÉ; CONCOURS D'INFRACTIONS; FIXATION DE LA PEINE; PEINE PÉCUNIAIRE | CPP.10; CP.25; CP.139; CP.47; CP.49; CP.34